The democratic uprising in North Africa Case study of Tunisia’s Jasmine revolution - Leksour, Nacer (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
Street vendor Mohamed Bouazizi’s self-immolation ignited protest throughout Tunisia in December 2010. Bouazizi’s response to the confiscation of his fruit cart by President Zine El Abidine Ben Ali’s regime officials resonated throughout Tunisia and the wider Arab world. A personal protest in a provincial city of Sidi Bouzid in Tunisia’s interior became the point of departure for the Arab “Spring”. In a matter of weeks, people were unified in a series of uprisings against their respective authoritarian governments. Driven by socio-economic deprivation, young politically disenfranchised, socially marginalized and unemployed citizens across the Middle East and North Africa (MENA) marched demanding a political voice. Tunisians triggered a wave of home-grown uprisings, many of which became revolutionary movements across the country.